2013
DOI: 10.1371/journal.pone.0069735
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in DNA-Repair Genes in a Cohort of Prostate Cancer Patients from Different Areas in Spain: Heterogeneity between Populations as a Confounding Factor in Association Studies

Abstract: BackgroundDifferences in the distribution of genotypes between individuals of the same ethnicity are an important confounder factor commonly undervalued in typical association studies conducted in radiogenomics.ObjectiveTo evaluate the genotypic distribution of SNPs in a wide set of Spanish prostate cancer patients for determine the homogeneity of the population and to disclose potential bias.Design, Setting, and ParticipantsA total of 601 prostate cancer patients from Andalusia, Basque Country, Canary and Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…We have recently reported differences in the distribution of genotypes within different populations of the same ethnicity (Henriquez- Hernandez et al 2013a), highlighting the importance of ethnic-specific differences in drug responsiveness (Yasuda et al 2008;Ma and Lu 2011). In the present paper, we observed that genotype distribution of 12 of 22 SNPs were statistically different among the studied populations.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…We have recently reported differences in the distribution of genotypes within different populations of the same ethnicity (Henriquez- Hernandez et al 2013a), highlighting the importance of ethnic-specific differences in drug responsiveness (Yasuda et al 2008;Ma and Lu 2011). In the present paper, we observed that genotype distribution of 12 of 22 SNPs were statistically different among the studied populations.…”
Section: Discussionsupporting
confidence: 50%
“…Geographical distribution of patients was as follows (Henriquez-Hernandez et al 2013a): 91 (15.14%) from Andalusia, 51 (8.48%) from Basque Country, 238 (39.60%) from Canary and 221 (36.77%) from Catalonia. All patients were of Spanish origin and all of them received written informed consent before sample collection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients were recruited from 4 different regions of Spain, as has been previously published [15]. As genotypic and allelic frequencies vary among subjects from these regions, and Andalusian patients showed the greatest differences [15,16], we excluded these subset of patients from further analyses to avoid bias. Patients who were initially operated were also excluded to form a homogenous group of patients with PCa.…”
Section: Patientsmentioning
confidence: 99%